Morphological and histological differences among three types of component roots and their differential contribution to water uptake in the rice root system. (2nd April 2020) - Watanabe, Yumika; Kabuki, Takuya; Kakehashi, Takahiro; Kano-Nakata, Mana; Mitsuya, Shiro; Yamauchi, Akira
ABSTRACT: The rice root system consists of three types of roots; main root, L-type and S-type lateral root (LR). These component roots are morphologically and histologically different, which is termed as heterorhizy. Root system hydraulic architecture is related to the unique features of component roots. We hypothesized that each component root contributes in different degrees to water uptake of the whole root system. Rice varieties IRAT 109 and Taichung 65 were grown in pots filled with soil under continuous waterlogged (CWL) and drought (CD) conditions until two weeks after heading. Morphology and histological structures of roots, which may regulate radial water movement, were compared among the three component roots. Moreover, hydraulic conductivity ( Lpr ) of the root system, which represents the water uptake ability, were measured with a pressure chamber. Based on a model that Lpr of the whole root system is a product of Lpr of each of the component roots and their surface areas, we found that the differences in Lpr between the two varieties and the plants grown under different soil water conditions for any of the component roots did not support the corresponding differences in the measured Lpr of the whole root system. In contrast, a significant and positive correlation was found between Lpr of the whole root system and the percentage of surface area of S-type LR but not for the other component roots. These results indicate S-type LR might have a higher contribution to Lpr of the whole root system than the other component roots. Graphical Abstract: